2018
DOI: 10.1016/j.jgo.2018.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Functional and cognitive impairment, social functioning, frailty and adverse health outcomes in older patients with esophageal cancer, a systematic review

Abstract: Functional and cognitive impairment, depression and social isolation are prevalent in patients with esophageal cancer, and associate with adverse health outcomes. Geriatric measurements may guide decision-making and customize treatments, but more large studies are needed to explore the clinical usability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Huang et al suggested EC patients aged ≥80 benefit from RT only if the cancer is in localized/regional stage (24). Functional and cognitive impairment, depression and social isolation are prevalent in older patients with esophageal cancer, and associate with adverse health outcomes (25). Thus, basically, advanced age itself is not enough reason to be excluded for RT.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al suggested EC patients aged ≥80 benefit from RT only if the cancer is in localized/regional stage (24). Functional and cognitive impairment, depression and social isolation are prevalent in older patients with esophageal cancer, and associate with adverse health outcomes (25). Thus, basically, advanced age itself is not enough reason to be excluded for RT.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors report numerous unmet physical, functional, psychosocial, and financial needs and problems with subsequent cancers, fatigue, pain, lymphedema, neuropathies, balance problems, mobility issues, bladder and bowel problems, dysphonia and other communication difficulties, dysphagia, cardiopulmonary and other end‐organ function declines, sexual dysfunction, depression and anxiety, and cognitive problems, among others . These problems can lead to reduced work productivity, quality of life, and survival . A confluence of several factors is limiting the resources of both health care systems and patients to offer and participate in needed follow‐up care services.…”
Section: The Need For Personalized Pathways For Cancer Follow‐up Carementioning
confidence: 99%
“…[8][9][10][11][12][13][14] These problems can lead to reduced work productivity, 15 quality of life, 16,17 and survival. [18][19][20][21][22] A conf luence of several factors is limiting the resources of both health care systems and patients to offer and participate in needed follow-up care services. These factors include: the growing number of survivors, especially those older than 65 years, who require the management of multiple comorbid conditions in addition to their cancer-specific concerns 2 ; health care provider shortages in oncology, primary care, and nursing [23][24][25][26] ; scarce provider education or training in how to provide cancer follow-up care, especially for the primary care workforce 27 ; and the increasing costs of cancer care 28 and posttreatment survivorship care.…”
mentioning
confidence: 99%
“…The most prevalent of these needs were fatigue, changes in sexual function, and changes in memory and concentration (physical); worry about cancer recurrence, changes in sexual intimacy, and depression (emotional); and challenges presented when returning to work/school, challenges getting to/from appointments, and paying for health care (practical). These ongoing issues can negatively impact survivors’ functional ability, survival, quality of life and their economic, emotional, and social wellbeing [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%